Cloning, expression and purification of Rattus norvegicus angiogenin - Giang Nguyễn Hoài; Soo-Ik, Chang; Phúc Nguyễn Hạnh (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 51-55, 2005